ANALISIS SISTEM INFORMASI MANAJEMEN DALAM STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM DI DAERAH PAMULANG - Achdiyat Ilyasa Samudra; Allyssa Zahra Azizah Salsabilla; Ferdi Nurochim; Nazdan Rosidin; Nazwa Lintang Seina; Samsoni; Aprinia Handayani (Journal of Research and Publication Innovation, 2024)
In the context of increasing competition in the local market, effective marketing strategies are crucial for Micro, Small and Medium Enterprises (MSMEs) in the Pamulang Region. This study aims to evaluate the role of management information systems in supporting marketing strategies to increase sales of MSME products. Through a systematic analysis approach, this research identifies the factors that influence MSME product sales and proposes the integration of management information systems as a solution to increase marketing effectiveness. The findings highlight the importance of using information technology in managing customer information, market analysis, and decision making which can help MSMEs in strengthening product visibility and expanding market share. The practical implications of this research provide guidance for MSME owners and marketing practitioners to optimize the use of technology in their marketing strategies, so as to increase competitiveness and business growth in this increasingly digital environment.